Glutathione revisited: a better scavenger than previously thought - Haenen, Guido R. M. M.; Bast, Aalt (Frontiers in Pharmacology, 2014)
Glutathione is the classical example of a scavenging antioxidant. It forms the first line of defense and efficiently scavenges reactive species, e.g. hypochlorous acid (HOCl), before they inflict damage to biomolecules. Glutathione is the classical example of a scavenging antioxidant. It forms the first line of defense and efficiently scavenges reactive species, e.g. hypochlorous acid (HOCl), before they inflict damage to biomolecules. Scavenging antioxidant activity is best established in competition assays (that closely mimics molecular mechanism of the biological effect). In this type of assay, the antioxidant competes with a molecule that functions as an easy read-out detector for a reactive species. It is generally assumed that the scavenging antioxidant activity reflects the reaction rate constant of the antioxidant with the reactive species (ka). However, critical appraisal of several competition assays of glutathione with HOCl as reactive species, reveals that ka does not determine the scavenging antioxidant activity. Assays using acetylcholine esterase, alpha1-antiprotease, methionine and albumin as detector are compared. The total number of molecules of the reactive species scavenged by glutathione plus that by partially oxidized forms of the glutathione, reflect the scavenging activity of glutathione. The contribution of the partially oxidized forms of glutathione depends on the reactivity of the competing molecule. In several assays the partially oxidized forms of glutathione have a substantial contribution to the scavenging activity of glutathione. In contrast to the prevailing perception, not the reaction rate but rather the total number of molecules of the reactive species scavenged reflects the true scavenging activity of an antioxidant like glutathione.